Microstructure evolution of steel-aluminum wire during deformation by "equal-channel angular pressing-drawing"method - Volokitina, I.E.; Volokitin, A.V.; Panin, E.A.; Latypova, M.A.; Kassymov, S.S. (Eurasian Physical Technical Journal, 2022)
During experimental studies of the equal-channel angular pressing-drawing effect on the microstructure evolution and mechanical properties change, the principal possibility and effectiveness of using the proposed continuous method for forming an ultrafine-grained structure and increasing the strength properties of steel-aluminum wire was proved. The deformation was carried out at ambient temperature in three passes. It is shown that both layers of bimetallic wire are processed unevenly. An aluminum shell with an initial grain size of 22 microns was processed up to 2 microns. The steel core has a different grain size in the transverse and longitudinal sections. With an initial grain size of 18 microns, after deformation the grain size is about 10 microns in the longitudinal section and 8 microns in the transverse section.
Keywords: severe plastic deformation; microstructure; bimetallic wire; steel; aluminum; mechanical properties